Transformation path of modern media from the perspective of internet of things - Yujie, Zhang; Yasin, Megat Al Imran; AlSagoff, Syed Agil; Ang, Lay Hoon (Hindawi, 2022)
The Internet of Things (IoT) is a new technology revolution that aims to link all ordinary physical items to the Internet, creating a massive worldwide network of uniquely connected things that can exchange information and fulfill planned activities, resulting in considerable advantages for consumers. Researchers have started to explore new techniques of technical help in various fields (e.g. health, transport, and education) as the Internet of Things has grown in popularity in recent years. In this research, we present a revolutionary IoT paradigm with an encryption mechanism to establish a kind of network that would allow the more intelligent media-data transfer. Initially, we collected COVID-19-related data and preprocessed the raw data using the median absolute deviation method. The preprocessed data that is to be transferred to the media is then stored in the IoT device using various sensors. To improve the security of the data, we propose Robust Modern Media Data Encryption (RMMDE) algorithm with Enhance Cuckoo Swarm Optimization (ECSO) algorithm. The suggested mechanism is compared to the traditional encryption approaches, and the metrics are evaluated using the OriginPro tool. This proposed methodology could be a start point for better and more efficient media data transmission.